Techno-Economical Evaluation of Bio-Oil Production via Biomass Fast Pyrolysis Process: A Review - Inayat, Abrar; Ahmed, Ashfaq; Tariq, Rumaisa; Waris, Ammara; Jamil, Farrukh; Ahmed, Shams Forruque; Ghenai, Chaouki; Park, Young-Kwon (Frontiers in Energy Research, 2022)
Biomass pyrolysis is one of the beneficial sources of the production of sustainable bio-oil. Currently, marketable bio-oil plants are scarce because of the complex operations and lower profits. Therefore, it is necessary to comprehend the relationship between technological parameters and economic practicality. This review outlines the technical and economical routine to produce bio-oils from various biomass by fast pyrolysis. Explicit pointers were compared, such as production cost, capacity, and biomass type for bio-oil production. The bio-oil production cost is crucial for evaluating the market compatibility with other biofuels available. Different pretreatments, upgrades and recycling processes influenced production costs. Using an energy integration strategy, it is possible to produce bio-oil from biomass pyrolysis. The findings of this study might lead to bio-oil industry-related research aimed at commercializing the product.